2010
DOI: 10.1063/1.3408289
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing water molecule distribution by atomic force microscopy

Abstract: Hydration structures at biomolecular surfaces are essential for understanding the mechanisms of the various biofunctions and stability of biomolecules. Here, we demonstrate the measurement of local hydration structures using an atomic force microscopy system equipped with a low-noise deflection sensor. We applied this method to the analysis of the muscovite mica/water interface and succeeded in visualizing a hydration structure that is site-specific on a crystal. Furthermore, at the biomolecule/buffer solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
185
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(199 citation statements)
references
References 20 publications
(22 reference statements)
8
185
3
Order By: Relevance
“…Both SFA and atomic force microscopy (AFM) have been used to probe the structure of hydration water (Jarvis et al 2000;Kimura et al 2010;Li et al 2007). We focus here on AFM because, in principle, through the use of narrow tips (e.g., carbon nanotubes), this method could be used to sample narrow surface regions commensurate to point defects and surface heterogeneities (Avanesyan et al 2005).…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…Both SFA and atomic force microscopy (AFM) have been used to probe the structure of hydration water (Jarvis et al 2000;Kimura et al 2010;Li et al 2007). We focus here on AFM because, in principle, through the use of narrow tips (e.g., carbon nanotubes), this method could be used to sample narrow surface regions commensurate to point defects and surface heterogeneities (Avanesyan et al 2005).…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…On the other hand, the importance of water distribution [7] and hydration in structural studies of biological macromolecules was directly shown by comparison of the AFM images of DNA obtained in air and in aqueous solutions [8]. The heights of DNA double helices and superhelices measured in air were more than twice lower than in water.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several methods have recently been proposed for imaging 3D distribution of forces acting on a tip (F t ) near the sample surface. [16][17][18][19][20][21] In these methods, a tip is scanned in Z direction (i.e. perpendicular to the surface) as well as in XY directions to image the whole 3D interfacial space.…”
mentioning
confidence: 99%